Propriedades elétricas de óxido de grafeno por microscopia de varredura - Salomão, Francisco Carlos Carneiro Soares (2015)
Potential applications of nanomaterials such as graphene and its derivatives, in electronic devices led to a detailed study of their electronic properties. The graphene oxide also has been proposed for various applications, of which we highlight the applications in composite thin films with supercapacitors properties. However, many of the graphene oxide properties can vary from sample to sample, which poses as an important setback to technological application of this material. Furthermore, the characterization electric and dielectric properties on nanomaterials is also a challenging task, since most characterization techniques have been developed for films thicker than 200 nm, which is much thicker than the atomically thin layer of graphene oxide. In this work, we studied the electric and dielectric properties of graphene oxide flakes by scanning probe microscopy. We use electrostatic force microscopy (EFM) to estimate the surface charge density of a layer of graphene oxide, as well as the nature of these charges. We also use the Kelvin force microscopy (KPFM) to characterize transparent thin films based on graphene oxide and Cellulose Acetate. KPFM was also used to determine the surface potential of graphene oxide as a function of humidity. Finally, we have applied the capacitance gradient (dC/dz), which is obtained by measuring the second harmonic signal in EFM to calculate the dielectric constant of monolayer and few-layer graphene oxide. As the dielectric constant cannot be extracted directly from the measurements, we developed an analytical model to describe the electric signal (dC/dz) for the system and show that this model can be used to estimate the dielectric constant of monolayer and few-layer graphene oxide.